THE CHINESE GOVERNMENT’S CULTURAL DIPLOMACY THROUGH PARTNERSHIP BETWEEN CONFUCIUS INSTITUTE AND MUSLIM UNIVERSITIES IN INDONESIA - Gabriella D Amelia; Adriani Isyana (AEGIS : Journal of International Relations, 2016)
One fact that is very often overlooked is that the ethnic Chinese in Indonesia, often referred to as Chinese Indonesians, play an important part in the diplomatic relations between Indonesia and People’s Republic of China (PRC.) The image that the majority Indonesians, especially the Muslim ones, have about the minority ethnic Chinese in Indonesia helps shape perspectives about PRC. Since the Chinese Indonesians have very often been discredited as pork-eating, ancestors-worshipping (which are deemed haram (forbidden) in Islam), rude, scheming, apolitical, greedy and only care about money, it is not a wonder that if coupled with the image of PRC as a closed country that is stuck in communism, the collective image of the Chinese in general can very well stand in the way of the two countries’ diplomatic relations. To counter this, in 2007 the PRC government through Confucius Institute launched partnerships with several major state and private universities in Indonesia. However, this essay focuses on Confucius Institute’s partnerships with Universitas Al-Azhar Indonesia (Al-Azhar University Indonesia (UAI)) in Jakarta and Universitas Muhammadiyah Malang (Muhammadiyah University Malang (UMM)) in Malang, East Java, as PRC government’s tool to engage Indonesia’s Muslim majority in cultural diplomacy for the success of PRC and Indonesia’s relations.